Advanced power electronics converters for future renewable energy systems - Priyadarshi, Neeraj (CRC Press, Taylor & Francis Group, 2023)
This book narrates an assessment of numerous advanced power converters employed on primitive phase to enhance the efficiency of power translation pertaining to renewable energy systems. It presents the mathematical modelling, analysis, and control of recent power converters topologies, namely, AC/DC, DC/DC, and DC/AC converters. Numerous advanced DC-DC Converters, namely, multi-input DC-DC Converter, Cuk, SEPIC, Zeta and so forth have been assessed mathematically using state space analysis applied with an aim to enhance power efficiency of renewable energy systems. The book:- Explains various power electronics converters for different types of renewable energy sources- Provides a review of the major power conversion topologies in one book- Focuses on experimental analysis rather than simulation work- Recommends usage of MATLAB, PSCAD, and PSIM simulation software for detailed analysis - Includes DC-DC converters with reasonable peculiar power ratingThis book is aimed at researchers, graduate students in electric power engineering, power and industrial electronics, and renewable energy